Prospects of Using the Cavitation Technologies in Transportation - Gurbanov, A.N.; Sardarova, I.Z. (Herald of Azerbaijan Engineering Academy, 2023)
The paper explores the aspects negatively affecting the pipeline transportation of heavy oil and reviews the implementation possibility of cavitation processes as an alternative method of solving occurring problems. Based on the laboratory research of abnormal oil from Azerbaijan fields, the parameters and technical upgrade of heavy oil in the system of hydrodynamic cavitation have been studied. Moreover, as a result of carried out experiment, the operation mechanism of cavitation process during reduction of heavy oil viscosity is described and the implementation prospect of this technology in commercial scales is analyzed as well.